Preventing stunting through food security and complementary feeding education at the Mujur Aisyiyah Community - Riyanti, Eka; Nurlaila, Nurlaila; Herniyatun, Herniyatun; Prayoga, Enggal Agus; Dewi, Nurlaely Kurnia; Pertiwi, Anandaru Putri Shindu; Sulasih, Umi (Community Empowerment, 2025)
Stunting remains a global problem with detrimental effects on children's growth and development. Specifically, Mujur Village has three toddlers suffering from malnutrition. However, health cadres of PRA Mujur still lack adequate knowledge and skills in handling stunting, particularly concerning complementary feeding (MP-ASI). The method employed was providing education to the cadres, in the form of material presentation, discussions, question-and-answer sessions, and video screenings. The results of the activity revealed an increase in knowledge after the education regarding food security and complementary feeding from 80.9 to 96.9. This had an impact on improving skills in preparing complementary feeding. Thus, this program is expected to reduce the stunting rate in Mujur Village to zero.